Peningkatan Kualitas Pembelajaran IPS Melalui Model Pembelajaran Teams Games Tournament (TGT) Siswa 4 Kelas III SDN 19 Salimpaung - Yulihartuti (Publikasi Indonesia, 2022)
The problem in this study is whether the learning outcomes of third grade students of SD Negeri Salimpaung can improve through the use of the Teams Games Tournament (TGT) Cooperative Learning Model. The purpose of this study was to improve the learning outcomes of third grade students of SD Negeri Salimpaung. The research method used was the class action research method (PTK) which was carried out at SD Negeri Salimpaung in the 2019/2020 academic year for Class III students totaling 26 students. The research design used is Classroom Action research. This research was carried out for two actions (cycles). Each action includes planning, implementation, observation and reflection. Data collection techniques through learning outcomes tests. The results showed that there was an increase in learning outcomes through the use of the Cooperative Learning Model of Teams Games Tournament (TGT) class III SD Negeri Salimpaung. The increase in this study is quite significant, namely from the average learning outcomes of cycle I of 71.25% to 80.42% in cycle II or an increase of 9.17%. The increase also occurred in the completeness of learning outcomes classically, from 60% in cycle I increased to 85% in cycle II or an increase of 25%. This means that the results obtained have met the criteria for classical student learning completeness as set out in the indicators of this study, namely 80% and the completeness of individual learning outcomes of 65.